76.5k views
1 vote
F(x)x=-2 x=3 f(x)x^3-1=?

User Jacory
by
4.9k points

1 Answer

0 votes

We want to find the average rate of change of the function


f(x)=x^3-1

On the interval;


x=-2,x=3

The average rate of change could be found by;


m=(f(3)-f(-2))/(3-(-2))
\begin{gathered} f(3)=3^3-1=27-1=26 \\ f(-2)=(-2)^3-1=-8-1=-9 \end{gathered}

Thus, the average rate of change m is;


\begin{gathered} m=(26-(-9))/(3-(-2)) \\ m=(35)/(5) \\ m=7 \end{gathered}

Therefore, the average rate of change of f(x) is 7

User Qerub
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.